Os tipos das construçõdes com clivagem em português - Mikołajczak, Sylwia (Wydawnictwo Naukowe UAM, 2003)
This paper deals with the four types of cleft constructions in Portuguese. As the mentioned constructions are deeply embedded in the emphatic process of focalisation, we try to give, in the introduction, elear definitions of the terms involved in the process, concentrating mainly on Focus and Topie. The corpus is constituted by the typology of the cleft constructions in Portuguese, containing pseudo-cleft, semipseudo-cleft, and the proper cleft constructions, as well as the “é que” structures. We try to make an analysis of the focus position in the samples coming from such authors as Casteleiro, Vilela, Sedano and our own examples. This paper is organised in three main parts: 1. Introduction; 2. Cleft construction types in Portuguese; 3. Conclusions.